Risk Benefit for EU - Partnering to strengthen the risk-benefit assessment within EU using a holistic approach: mid-term report - Alvito, Paula (2019)
RiskBenefit4EU – Partnering to strengthen the risk-benefit assessment within EU using a holistic approach (RB4EU) is a project funded by European Food Safety Authority (EFSA) under Partnering Grants (GP/EFSA/AFSCO/2017/01) and was launched on the 17th January 2018, at a kick-off meeting in the EFSA’s premises, Parma, Italy. With the focus on the capacity building, it aims to develop a strategy to strengthen the EU capacity to assess and integrate food risks and benefits in the areas of microbiological, nutritional and chemical components through the development of a harmonized framework that will be available to EU member states organizations. Within the 1st year of the project, several deliverables and expected outputs were attained, including: two submitted manuscripts, eight communications in national and international conferences, one mid-report, two training activities, one harmonized risk-benefit assessment (RBA) framework on RBA capacity building, one flyer, a project website and one international workshop and the respective abstracts book. In order to answer to specific project and team member’s needs, some adjustments concerning the team composition and the budget allocated to travels and missions were performed, all in agreement with EFSA. RB4EU allowed to gather, for the first time, a multidisciplinary team to develop a capacity building framework on RBA in foods. After the first year of the project, the team and the capacity building framework on RBA in foods are consolidated, allowing to progress on the Portuguese case-study involving data at national level on nutritional, toxicological and microbiological areas. A close collaboration between team members and EFSA have been developed promoting an important support for the project progress.